1893
DOI: 10.1002/ange.18930061702
|View full text |Cite
|
Sign up to set email alerts
|

Über die Anwendung des Furfurols als Reagens zur Erkennung des Sesamöls in Ölmischungen

Abstract: Über die Anwendung des Furftirols als Reagens zur Erkennung des Sesamöls in Olmischungen. Von V. Villavecchia und G. Fabris.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1911
1911
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The term sesamol was coined by Hans Kreis in 1903 for yet unidentified phenolic product of sesame responsible for color tests used to identify sesame oil [ 118 ] (see also Section 2.5.2 ). Kreis was apparently unaware of Villavecchia and Fabris work from 1893 [ 119 ]. The structure of sesamol was established four years later [ 79 , 80 ].…”
Section: Chemistry Of Sesame Lignansmentioning
confidence: 99%
See 1 more Smart Citation
“…The term sesamol was coined by Hans Kreis in 1903 for yet unidentified phenolic product of sesame responsible for color tests used to identify sesame oil [ 118 ] (see also Section 2.5.2 ). Kreis was apparently unaware of Villavecchia and Fabris work from 1893 [ 119 ]. The structure of sesamol was established four years later [ 79 , 80 ].…”
Section: Chemistry Of Sesame Lignansmentioning
confidence: 99%
“…Before chromatography became established in the analysis of sesame oil, color reactions and photometry in UV light were used to detect certain lignans and semi-quantitatively estimate their concentration. Villavecchia’s colorimetric test [ 119 ] was established to distinguish sesame oil from other oils and to differentiate butter from margarine ( Figure 7 ), which was labeled with 5–10% sesame oil in the first half of the 19th century [ 122 , 187 ]. Villavecchia test became the official method of the American Oil Chemists’ Society for the detection of sesame oil in vegetable and animal oils and fats [ 188 ].…”
Section: Chemistry Of Sesame Lignansmentioning
confidence: 99%
“…A number of authors reported melting points for this sterol(s) ranging from 130°to 139°C. (188,198,242,243). Villavecchia and Fabris (242,243) reported the sterol(s) to have an optical activity of [a] n°°= -34°23', while Marcusson and Meyerheim (154) found it to be [a] p°°= -23°.…”
Section: Phytosterolmentioning
confidence: 99%
“…(188,198,242,243). Villavecchia and Fabris (242,243) reported the sterol(s) to have an optical activity of [a] n°°= -34°23', while Marcusson and Meyerheim (154) found it to be [a] p°°= -23°. The acetyl derivative has been reported to melt between 125°and 131°C.…”
Section: Phytosterolmentioning
confidence: 99%